The effect of trust, perceived risk and satisfaction on the repurchase intention of Shopee application users - Adella Cunrawasih; Awisal Fasyni (Marketing Management Studies, 2023)
The purpose of this study is to examine how Trust, Perceived Risk, and Satisfaction impact Repurchase Intentions in the Shopee application Padang City. All Shopee application users in Padang City who had used the app at least once for online purchasing throughout the previous six months made up the study's population. 140 respondents made up the samples used in this investigation. Online surveys are used to gather data, while SPSS software is used to handle the data. This study's findings support it. Users of the Shopee application in the city of Padang's Repurchase Interest are positively and significantly impacted by trust. Users of the Shopee application in the city of Padang have a negative and significant impact on their interest in repurchasing goods due to their perception of risk. Users of the Shopee application in the city of Padang's Repurchase Interest are positively and significantly impacted by satisfaction. The findings of this study indicate that trust and contentment have a positive and significant influence, whereas the perception of risk has a negative affect.